Tobacco use prevalence, knowledge, and attitudes among newly diagnosed tuberculosis patients in Penang State and Wilayah Persekutuan Kuala Lumpur, Malaysia - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki; Abd Aziz, Noorizan; Syed Sulaiman, Syed Azhar; Mohamad Noordin, Noorliza; Muttalif, Abdul Razak; Ahmad Mahayiddin, Aziah (BioMed Central, 2010)
Background There is sufficient evidence to conclude that tobacco smoking is strongly linked to tuberculosis (TB) and a large proportion of TB patients may be active smokers. In addition, a previous analysis has suggested that a considerable proportion of the global burden of TB may be attributable to smoking. However, there is paucity of information on the prevalence of tobacco smoking among TB patients in Malaysia. Moreover, the tobacco-related knowledge, attitudes, and behaviors of TB patients who are smokers have not been previously explored. This study aimed to document the prevalence of smoking among newly diagnosed TB patients and to learn about the tobacco use knowledge and attitudes of those who are smokers among this population.